Visualization of the intrarenal distribution of capillary blood flow. Issue 8 (22nd April 2019) - Fan, Letao; Wang, Shaoxun; He, Xiaochen; Gonzalez‐Fernandez, Ezekiel; Lechene, Claude; Fan, Fan; Roman, Richard J.
Abstract: This study describes a modified technique to fill the renal vasculature with a silicon rubber (Microfil) compound and obtain morphologic information about the intrarenal distribution of capillary blood flow under a variety of conditions. Kidneys and cremaster muscles of rats were perfused in vivo with Microfil using a perfusion pressure equal to the animal's mean arterial pressure at body temperature. Microfil did not alter arteriolar diameter or the pattern of flow in the microcirculation of the cremaster muscle. The modified protocol reproducibly filled the renal vasculature, including; glomerular, peritubular, and vasa recta capillaries. We compared the filling of the renal circulation in control rats with that seen in animals subjected to maneuvers reported to alter the intrarenal distribution of blood flow. Infusion of angiotensin II, hypotension, volume expansion, and mannitol‐ or furosemide‐induced diuresis redistributed flow between renal cortical and medullary capillaries. The advantage of the current technique is that it provides anatomical information regarding the number, diameter, and branching patterns of capillaries in the postglomerular circulation critical in determining the intrarenal distribution of cortical and medullary blood flow. Abstract : This study describes a modified technique to fill the renal vasculature with a silicon rubber (Microfil) compound and obtain morphologic information about the intrarenal distribution of capillary blood flow regarding the number, diameter, and branching patterns of capillaries in the postglomerular circulation critical in determining the mechanisms involved in the redistribution of blood flow in the kidney under a variety of conditions.